Clutter evalution of unmanned surface vehicles for maritime traffic monitoring - Nadiy Zaiaami, Muhammad; Abd Rashid, Nur Emileen; Ismail, Nor Najwa; Ibrahim, Idnin Pasya; Enche Ab Rahim, Siti Amalina; Zalina Zakaria, Nor Ayu (Institute of Advanced Engineering and Science, 2024)
A traditional maritime radar system is utilized for ship detection and tracking through onshore transmitters and receivers. However, it faces challenges when it comes to detecting small boats. In contrast, unmanned surface vehicles (USVs) have been designed to monitor maritime traffic. They excel in detecting vessels of various sizes and enhance the capabilities and resolution of maritime radar systems. Nevertheless, just like conventional radar systems, USVs encounter difficulties due to environmental interference and clutter, affecting the accuracy of target signal detection. This research proposes a comprehensive numerical assessment to tackle the clutter issue associated with USVs. This involves gathering clutter signal data, performing numerical analysis, and employing distribution fitting techniques that leverage mathematical distributions to unravel data complexity. The root mean square error (RMSE) is applied in this analysis to validate the efficacy of the distribution model. The results of this study aim to formulate a clutter model that can enhance radar performance in detecting small vessels within cluttered environments.